2014 CVM News: Iceland president visits Cornell and the College: Green energy forges good business - Office of Marketing and Communications. Media Relations (Cornell University, College of Veterinary Medicine, 2014)
This news item from the Cornell Chronicle is about: Explaining how Iceland tapped into the Earth for geothermal energy and captured water resources to develop renewable electricity, Ólafur Ragnar Grímsson, president of Iceland, told a Cornell audience how his country remade itself from one of Europe’s poorest into a nation that is financially and environmentally secure.